Motivation and Facilities to the Compliance of Independent Midwife Practices in Recording Reporting on Maternal Child Health Services in Wonosobo - Setiasih .; Gunarmi .; Siswanto Pabidang (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Independent Practice Midwives are obliged to systematically record midwifery care and other services provided, the Wonosobo Health Office and the professional organization of the Indonesian Midwifery Association have not yet made a mutual agreement on the report form in which PMB is required to report records of Maternal and Child Health services to Puskesmas every year. month. Purpose this study was to determine the relationship between motivation and facilities on PMB compliance. Type of research is a quantitative with a cross sectional research design. Subjects was 210 PMB with a significance level of 1%, so the samples taken were 160. Sample was determined randomly using a lottery system. The data were taken using a questionnaire that had been tested for validity and reliability. Data analysis consisted of Chi Square statistical test and logistic regression analysis. The results show that there is a significant positive relationship between motivation and compliance, the value of continuity correction is 57,325 p-value = 0.0000 (p<0.05). There is a significant positive relationship between facilities and compliance with the value of continuity correction 50.897 p-value = 0.0000 (p<0.05). The motivation and facilities variables simultaneously have a significant effect on the compliance variable because the omnibus test significance value is 0.000 (p<0.01) with the coefficient of determination R square. It is explained that the motivation and facilities variables in the study are able to contribute to the compliance variable of 0.668 (66.8 %), sequentially the most influential variable on Compliance is the Motivation variable with a wald value of 29,827 followed by the Facility variable with a wald value of 26,719.